The Determinants of Convention Participants’ Intention to Revisit the Hosting Destination - Ho, Jie Min (Curtin University, 2021)
This thesis examined the determinants of convention participants’ revisit intention to the hosting destination. Using the Partial Least Squares- Structural Equation Modelling, the results demonstrated that both perceived value and value of co-creation shaped participants’ attitude and their subsequent intention to revisit the hosting destination. This study offered new perspectives on the areas where convention participants see important and conclusively proved that convention hosting is an effective strategy in encouraging future leisure travel intention among convention participants.